SWK-11. ASSESSMENT OF THE INDIRECT COSTS ASSOCIATED WITH PROTON THERAPY TREATMENT FOR ALBERTA PATIENTS REFERRED OUT OF COUNTRY. (4th December 2020) - Black, Karina; Middleton, Jackie; Ghosh, Sunita; Eisenstat, David; Patel, Samor
Abstract: BACKGROUND: Proton therapy for benign and malignant tumors has dosimetric and clinical advantages over photon therapy. Patients in Alberta, Canada are referred to the United States for proton treatment. The Alberta Heath Care Insurance Plan (AHCIP) pays for the proton treatment and the cost of flights to and from the United States (direct costs). This study aimed to determine the out-of-pocket expenses incurred by patients or their families (indirect costs). METHODS: Invitation letters linked to an electronic survey were mailed to patients treated with protons between 2008 and 2018. Expenses for flights for other family members, accommodations, transportation, food, passports, insurance, and opportunity costs including lost wages and productivity were measured. RESULTS: Fifty-nine invitation letters were mailed. Seventeen surveys were completed (28.8% response rate). One paper survey was mailed at participant request. Nine respondents were from parent/guardian, 8 from patients. All patients were accompanied to the US by a family member/friend. Considerable variability in costs and reimbursements were reported. Many of the accompanying family/friends had to miss work; only 3 patients themselves reported missed work. Time away from work varied, and varied as to whether it was paid or unpaid time off. CONCLUSIONS: Respondents incurred indirect monetary and opportunity costs which were not covered by AHCIP when traveling out of country for proton therapy. Prospective studies could help provide current data minimizing recall bias. These data may be helpful for administrators in assessing the societal cost of out-of-country referral of patients for proton therapy.